2022
DOI: 10.5694/mja2.51517
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and genetic features of hereditary pancreatitis in South Australia

Abstract: Objective To characterise the clinical phenotypes and genetic variants of hereditary pancreatitis in people diagnosed in South Australia. Design, setting, participants Cross‐sectional study of people who received molecular diagnoses of hereditary pancreatitis from one of four major diagnostic services in South Australia, 1 January 2006 – 30 June 2021. Main outcome measures Genotypic and clinical features of people with hereditary pancreatitis, including age at onset, attack frequency, pain indices, use of opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Genetic mutations (Table 1) seem to account for the majority of such cases [1,4,5] where an actual aetiology can be defined. This dates from 1996 and a report by Whitcomb et al [6] that identified mutations in PRSS1 (Protein Serine type 1) in families from Kentucky and West Virginia who had children and young adults with CP, which was later confirmed in other studies [1,7,8]. Since then, other genes have been identified, including SPINK1 (serine protease inhibitor kazal type 1) [1,[9][10][11], CFTR (cystic fibrosis transmembrane conductance regulator) [12][13][14], CPA1 (carboxypeptidase A1) [15], CTRC (chymotrypsin C) [5,[16][17][18], CLND2 (claudin-2) [19], and perhaps CELA3B (chymotrypsin-like elastase family member 3B) [20].…”
Section: Demographics and Aetiologymentioning
confidence: 80%
See 2 more Smart Citations
“…Genetic mutations (Table 1) seem to account for the majority of such cases [1,4,5] where an actual aetiology can be defined. This dates from 1996 and a report by Whitcomb et al [6] that identified mutations in PRSS1 (Protein Serine type 1) in families from Kentucky and West Virginia who had children and young adults with CP, which was later confirmed in other studies [1,7,8]. Since then, other genes have been identified, including SPINK1 (serine protease inhibitor kazal type 1) [1,[9][10][11], CFTR (cystic fibrosis transmembrane conductance regulator) [12][13][14], CPA1 (carboxypeptidase A1) [15], CTRC (chymotrypsin C) [5,[16][17][18], CLND2 (claudin-2) [19], and perhaps CELA3B (chymotrypsin-like elastase family member 3B) [20].…”
Section: Demographics and Aetiologymentioning
confidence: 80%
“…Genetic mutations (Table 1) seem to account for the majority of such cases [1,4,5] where an actual aetiology can be defined. This dates from 1996 and a report by Whitcomb et al [6] that identified mutations in PRSS1 (Protein Serine type 1) in families from Kentucky and West Virginia who had children and young adults with CP, which was later confirmed in other studies [1,7,8]. Since then, other genes have been identified, including SPINK1 (serine…”
Section: Demographics and Aetiologymentioning
confidence: 87%
See 1 more Smart Citation